THE EFFECT OF COMPENSATION AND COMMITMENT TO EMPLOYEE MOTIVATION IN A SUB-DISTRICT PALEMBANG - Gunarto, Muji; Yunilda; Yessy Widiastuty (Dinasti International Journal of Management Science, 2020)
This study aims to analyze and explain the effect of compensation and commitment to employee motivation. The type of research used is associative research by using quantitative methods. The number of samples used was 100 (one hundred) employees in A Sub-District, Palembang. The sampling technique was carried out randomly and the data analysis used was structural equation modeling (SEM). The results showed that the t-value for compensation 0.44 (<1.96) so that compensation did not significantly influence the motivation of A Subdistricts in Palembang. While the t-value for commitment was 4.42 (> 1.96), so commitment has a positive and significant effect to employee motivation. Therefore a strong commitment is needed to increase employee motivation.